CORRELATION BETWEEN MORAL KNOWLEDGE WITH MORAL ACTION OF PANCASILA'S VALUES AT CIVIC EDUCATION PROGRAM'S STUDENTS IN RIAU UNIVERSITY - Sunardi, Erma; Thalib, Zahirman; Hambali, Hambali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: this study aimed to find out the suitability fenomenal of moral knowledge and moral action that applied in daily life. The problem of this study, how does the correlation between moral knowledge with moral action of Pancasila's values at civic education program's students in riau university?. The samples of this study consist of 44 students. 9 students of senior students, 15 students of third year students, 8 students of second year students and 12 students of first year students. To choose the samples, the writer used purpossive sampling technique. The instrument of the study is using questionnaire that consists of 15 question about moral knowledge and 10 questions about moral action. The data was analyzed by qualitative descriptive and using spss 18.0 version. The result showed that the hypothesis of